Lugar de criança é no Youtube? Práticas discursivas dos novos formatos da publicidade infantil no Canal de Julia Silva - Oliveira, Renata Alves de Carvalho (2019)
In addressing the contemporary category of subjectivity, attention should be paid to various aspects of their production methods. Among them, media and technology seem to have considerable influence, being, at the present time, object of study of several researchers, in several fields of knowledge, including Psychology. The two carriers are even responsible for providing knowledge capable of informing us how to educate and how to shape our bodies, interlining, for example, our relations with one another and with oneself. Among the numerous communication and sharing networks created in the digital age, we can highlight YouTube. This digital video distribution platform was established in 2005 and it stands out not only adults as content producers, the so-called youtubers, but also children. In Brazil, the audience of junior youtubers channels has grown significantly in recent years, especially for Julia Silva channel. This is a YouTube channel with more than 4 million subscribers in which a child weekly posts videos on topics related to children's universe such as toys and school supplies. This research aims to investigate the discursive practices related to consumption that are addressed to children on Julia Silva Youtube channel. Discursive practices are forms of action in the world, practices that cause effects. Foucault adopted this concept to express the conditions of use of statements sets, discourses or discursive formations, which constitute the exercise of knowledge, operating and exercising powers. In order to achieve the aforementioned goal, six Júlia Silva’s videos with more views were analyzed using some tools of Foucaultian discourse analysis. In order to base our analysis theoretically, different authors were used: Foucault, Ferry, Postman, Sibilia, Miranda, Fischer, among others. All with the common interest of examining contemporary subjectivities. As a main result, this research found that children's advertising speech has spread to YouTube, mainly through junior YouTubers channels that use advertising strategies (merchandising, unboxing, product placement and sponsorship) in the promotion of all kinds of products related to infant universe. It is worth mentioning that this research also found a relevant factor in relation to childhood, the fact that the child, previously enunciated by adults, now comes in a place of self-enunciation. This research concluded that consumption is strongly present in the discursive practices set out by the studied youtuber channel, it was also possible to conclude that these discursive practices are responsible for the construction of a way of being a child in contemporaneity.